Replacing dietary antibiotics with 0.20% l-glutamine in swine nursery diets: impact on intestinal physiology and the microbiome following weaning and transport - Duttlinger, Alan W (J Anim Sci, 2021)
Previous research demonstrates that supplementing 0.20% l-glutamine (GLN) in the diets of newly weaned and transported pigs improves growth rate to a similar extent as providing dietary antibiotics (AB). However, research comparing the effects of GLN vs. AB on intestinal physiology and the microbiome is limited. Therefore, the study objective was to compare the effects of supplementing nursery diets with GLN, AB, or no dietary antibiotics (NA) on intestinal physiology and the microbiome of pigs in a production environment following weaning and transport. Mixed-sex piglets (N = 480; 5.62 ± 0.06 kg body weight [BW]) were weaned (18.4 ± 0.2 d of age) and transported for 12 h in central Indiana, for two replicates, during the summer of 2016 and the spring of 2017. Pens were blocked by BW and allotted to one of the three dietary treatments (n = 10 pens/dietary treatment/replicate [8 pigs/pen]): AB (chlortetracycline [441 ppm] + tiamulin [38.6 ppm]), GLN (0.20% as-fed), or NA fed for 14 d. From day 14 to 34, pigs were fed common AB-free diets in two phases. On day 33, villus height:crypt depth tended to be increased (P = 0.07; 7.0%) in GLN and AB pigs vs. NA pigs. On day 33, glucagon-like peptide 2 (GLP-2) mRNA abundance was decreased (P = 0.01; 50.3%) in GLN and NA pigs vs. AB pigs. Crypt depth was increased overall on day 33 (P = 0.01; 16.2%) during the spring replicate compared with the summer replicate. Villus height:crypt depth was reduced (P = 0.01; 9.6%) during the spring replicate compared with the summer replicate on day 33. On day 13, tumor necrosis factor-alpha and occludin mRNA abundance was increased (P ≤ 0.04; 45.9% and 106.5%, respectively) and zonula occludens-1 mRNA abundance tended to be greater (P = 0.10; 19.2%) in the spring replicate compared with the summer replicate. In addition, AB pigs had increased (P = 0.01; 101.3%) GLP-2 mRNA abundance compared with GLN and NA pigs. Microbiome analysis indicated that on day 13, dietary treatment altered the microbiota community structure (P = 0.03). Specifically, the AB pigs tended to be distinct from both the NA and GLN pigs (P = 0.08), and Lactobacillus was increased nearly 2-fold in AB compared with NA pigs (q = 0.04) and GLN pigs (q = 0.22). In conclusion, GLN supplementation tended to improve some morphological markers of intestinal health similarly to AB pigs, while the microbiome composition in GLN pigs was more similar to NA pigs than AB pigs.